Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.7554/elife.75878
|View full text |Cite
|
Sign up to set email alerts
|

Active morphogenesis of patterned epithelial shells

Abstract: Shape transformations of epithelial tissues in three dimensions, which are crucial for embryonic development or in vitro organoid growth, can result from active forces generated within the cytoskeleton of the epithelial cells. How the interplay of local differential tensions with tissue geometry and with external forces results in tissue-scale morphogenesis remains an open question. Here, we describe epithelial sheets as active viscoelastic surfaces and study their deformation under patterned internal tensions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…6 Furthermore, at large extensile activity, such a vortices-mediated flattening can result in a fusion of the internal leaflet of the shell, which eventually drives a transition from spherical to toroidal topology. Something related has recently be observed by Khoromskaia and Salbreux 72 and in the context of elastic sheets by Pearce et al 22…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…6 Furthermore, at large extensile activity, such a vortices-mediated flattening can result in a fusion of the internal leaflet of the shell, which eventually drives a transition from spherical to toroidal topology. Something related has recently be observed by Khoromskaia and Salbreux 72 and in the context of elastic sheets by Pearce et al 22…”
Section: Discussionsupporting
confidence: 62%
“…6 Furthermore, at large extensile activity, such a vortices-mediated flattening can result in a fusion of the internal leaflet of the shell, which eventually drives a transition from spherical to toroidal topology. Something related has recently be observed by Khoromskaia and Salbreux 72 and in the context of elastic sheets by Pearce et al 22 To better understand the pathway leading to the formation of protrusions, we focused on active nematic shells and showed that, for large extensile activity and after two oscillatory regimes (Fig. 6), protrusions appears as the result of the merging of pairs of +1/2 disclinations into asters.…”
Section: Discussionsupporting
confidence: 57%
“…To understand these results, we consider a simplified model of the Hydra's tissue, ignoring its bilayer structure and regarding the tissue as a closed 2D surface 38 with a minimal coupling of its curvature to the Ca 2+ field,  , given by the Jackiw-Teitelboim action 39,40 :…”
Section:   = −mentioning
confidence: 99%
“…Mathematically, the development of theory that couples hydrodynamics to surface geometry has led to many interesting predictions on the role of viscous forces in the ordering and shaping of membranes in both isotropic (Steigmann 1999;Hu, Zhang & Weinan 2007;Arroyo & DeSimone 2009;Rangamani et al 2013;Sahu et al 2020a;Tchoufag, Sahu & Mandadapu 2022) and ordered (Napoli & Vergori 2016;Nestler & Voigt 2022) fluids. Of particular note has been the inclusion of activity, leading to a variety of interesting morphodynamical phenomena and instabilities (Salbreux & Jülicher 2017;Bächer et al 2021;Khoromskaia & Salbreux 2023;Rank & Voigt 2021;Alert 2022;Bell et al 2022;Hoffmann et al 2022;Nestler & Voigt 2022;Salbreux et al 2022;Vafa & Mahadevan 2022) and even some attempts to construct rigorous shell theories of active materials (da Rocha, Bleyer & Turlier 2022). Much of this work has been driven by the desire to develop theories capable of describing the dynamics and morphogenesis of biological tissues and organisms (Jülicher, Grill & Salbreux 2018;Al-Izzi & Morris 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note has been the inclusion of activity, leading to a variety of interesting morphodynamical phenomena and instabilities (Salbreux & Jülicher 2017; Bächer et al. 2021; Khoromskaia & Salbreux 2023; Rank & Voigt 2021; Alert 2022; Bell et al. 2022; Hoffmann et al.…”
Section: Introductionmentioning
confidence: 99%